Risk of Adverse Pregnancy Outcomes by Prepregnancy Body Mass Index: A Population-Based Study to Inform Prepregnancy Weight Loss Counseling. Issue 1 (January 2015) - Schummers, Laura; Hutcheon, Jennifer A.; Bodnar, Lisa M.; Lieberman, Ellice; Himes, Katherine P.
Abstract : OBJECTIVE: To estimate the absolute risks of adverse maternal and perinatal outcomes based on small differences in prepregnancy body mass (eg, 10% of body mass or 10–20 pounds). METHODS: This population-based cohort study (N=226, 958) was drawn from all singleton pregnancies in British Columbia (Canada) from 2004 to 2012. The relationships between prepregnancy body mass index (BMI) (as a continuous, nonlinear variable) and adverse pregnancy outcomes were examined using logistic regression models. Analyses were adjusted for maternal age, height, parity, and smoking in pregnancy. Adjusted absolute risks of each outcome are reported according to incremental differences in prepregnancy BMI and weight in pounds. RESULTS: A 10% difference in prepregnancy BMI was associated with at least a 10% lower risk of preeclampsia, gestational diabetes, indicated preterm delivery, macrosomia, and stillbirth. In contrast, larger differences in prepregnancy BMI (20–30% differences in BMI) were necessary to meaningfully reduce risks of cesarean delivery, shoulder dystocia, neonatal intensive care unit stay 48 hours or longer, and in-hospital newborn mortality. Prepregnancy BMI was not associated with risk of postpartum hemorrhage requiring intervention, severe maternal morbidity or maternal mortality, or spontaneous preterm delivery before 32 weeks of gestation. CONCLUSION: These results can inform prepregnancy weight loss counseling by defining achievable weight loss goals for patients that may reduce their risk of poor perinatal outcomes. LEVEL OF EVIDENCE: II Abstract : Small differences in prepregnancy body mass index are associated with meaningfully lower preeclampsia, gestational diabetes, indicated preterm delivery, macrosomia, and stillbirth risks, whereas larger differences are necessary for other outcomes.